Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Kepatuhan Masyarakat Penerima Sertipikat Ptsl “Non PBB” Terhadap Pembayaran Pajak Bumi Dan Bangunan Di Kelurahan Girian Indah - Tawaluyan, Marthen Hansen; Katiandago, Theodora Maulina; Kepel, Rene Charles (Sam Ratulangi University, 2023)
This research aims to analyzed the factors that affected the compliance behavior of the PTSL certificate recipients that have not who are not yet compliant in fulfilling their responsibility in paying property tax. This research was conducted in July till September 2022. The research method used in this research is Quantitative research. The results of the hypothesis by using the multiple regression linear formula showed that 1) The understanding regarding taxation does not significantly affected the compliance of PTSL certificate recipients in paying property tax in Girian Indah. Whether the people of Girian Indah understand about taxation does not causing meaningful impact for them to comply; 2) The awareness of paying taxes has a positive and significant impact to the PTSL certificate recipients compliance in paying property tax in Girian Indah. The higher the awareness of the taxpayer the higher the compliance of the people to pay their property tax; 3) Income has positive and significant effect to the compliance behavior of the PTSL certificate recipients in paying their property tax in Girian Indah. The higher the income of the taxpayer the higher the obedience of the people of Girian Indah to pay their property tax; 4) The quality of service has a positive and significant impact to the compliance behavior of the PTSL certificate recipients to pay their property tax in Girian Indah. The better the service provided by the tax officer, the higher the level of taxpayer compliance in paying property tax; 5) tax sanctions have a positive and significant effect on the compliance of PTSL certificate recipients in paying property tax in Girian Indah. The higher the tax sanctions given to taxpayers, the more obedient taxpayers will be in paying property tax.